Interculturalidad y migración académica de estudiantes de El Oro en la Universidad Católica de Cuenca-Sede Azogues - Argudo Garzón, Antonio Lenin (2017)
This paper has as main objective the analysis of the social and cultural reality in which young immigrants from El Oro province who study in the Catholic University of Cuenca-Azogues Branch, to establish their perception about the intercultural relationship developed with the University community and the Azogues society. The methodology worked has a qualitative and ethnographic focus, and it is exploratory and descriptive in nature, gathering information from in-depth interviews with students who took part in the research. The research showed the perception of El Oro’s students regarding their integration in the society and their opportunity to exchange cultural aspects. It was concluded that the university community has become a bridge of integration between Orenses and Azogueños. However, these exchanges are spontaneous and do not have processes built by the institution of higher education or local authorities. Finally, there are social stereotypes and discrimination and these further complicate the creation of these intercultural spaces.